1999
DOI: 10.1007/s003300050675
|View full text |Cite
|
Sign up to set email alerts
|

Is there still a place for angiography in the management of renal mass lesions?

Abstract: In recent years, the development of noninvasive imaging modalities for exploration of the kidney has markedly reduced the use of angiography in the evaluation of renal masses. Presently, it is not required in routine practice to evaluate renal masses. Ultrasound is the most efficient procedure in detecting renal tumor. It is acknowledged that arteriography has a limited diagnostic and staging value compared with CT and MRI for the assessment of renal cell carcinomas (RCC). Most urologists recommend partial nep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 19 publications
0
27
0
2
Order By: Relevance
“…The development of angiographic suites, catheters, guidewires, and materials for embolization has offered alternative therapeutic options for patients prior to surgery [12] . The fi rst elective embolization of the renal artery was performed in 1973 [9] , and since then several reports have been published [4,11,[13][14][15] .…”
Section: Discussionmentioning
confidence: 99%
“…The development of angiographic suites, catheters, guidewires, and materials for embolization has offered alternative therapeutic options for patients prior to surgery [12] . The fi rst elective embolization of the renal artery was performed in 1973 [9] , and since then several reports have been published [4,11,[13][14][15] .…”
Section: Discussionmentioning
confidence: 99%
“…The reported rate of complications associated with palliative embolization is as high as 10-20%, with a mortality rate of 3.3%; the overall rate of complications (palliative and preoperative TAE) is 4.9%, with a mortality rate of 1.2% [13,30]. The major reported complications are renal failure and renal abscess.…”
Section: Discussionmentioning
confidence: 91%
“…TAE has produced good initial results, but is generally used for the palliative treatment of tumor-related signs and symptoms, such as gross hematuria, in patients with advanced RCC [29]. Moreover, some researchers have reported that TAE has yielded disappointing results with a high rate of complications [13,30]. Our study was based on the premise that TAE may contribute to longer survival provided it is as effective as nephrectomy.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, there is no consensus in the centers using this method about the necessity of imaging modalities demonstrating the anatomy of renal vascular system preparation (4).…”
Section: Introductionmentioning
confidence: 99%